Substance Use Disorder: Prenatal, Intrapartum and Postpartum Care. Issue 5 (September 2019) - Mahoney, Kathleen; Reich, Wendy; Urbanek, Susan
Abstract : Abstract: The growing opioid crisis in the United States affects childbearing women and their infants at an alarming rate. Substance use disorders in pregnancy have transitioned from a topic barely addressed to one that has become mainstream in the issue of pregnancy management. Opioid use can include appropriate use of a prescribed medication, the misuse of street drugs, and maintenance on an opioid agonist treatment such as methadone. Identifying this population of childbearing women is critical to be able to organize the appropriate resources and to provide a comprehensive multidisciplinary evidence-based plan of care. All clinicians need to be educated in identifying and caring for the growing population of women with substance use disorders. Each component of the continuum from prenatal care, labor and birth, and postpartum has challenges and issues that can have a positive or negative impact on the outcome of the pregnancy and the mother–infant relationship. Risk assessment, medication-assisted treatment, pain management, and fostering maternal–infant bonding are important considerations in the care of the woman with substance use disorder. Unbiased empathetic nurses are well positioned to strongly advocate and intervene on behalf of women with substance use disorder, which in turn will help to create positive outcomes for the mother and her baby. Abstract : There has been a dramatic increase in the United States in the number of women who present with substance use disorder during pregnancy. An overview of care for women with substance use disorder during the childbearing process continuum is provided.